Modeling and positive reinforcement techniques in improving children’s fine motor skills - Zahra, Fatimatuz; Lestari, Rahayu Puji; Sholichah, Ima Fitri (Universitas Mercu Buana Yogyakarta, 2024)
Education is something that cannot be underestimated, especially for children. With education, children can develop their creativity. However, there are still many children who do not receive proper education, so this has an impact on children's low fine motor skills. This research aims to determine the effectiveness of playdough modelling techniques and positive reinforcement techniques in improving fine motor skills in children of the Taman Baca Dadali Community in Gresik. The method used in this research is a quasi-experiment using a one-group pretest posttest research design. The subjects in this research were 7 people with characteristics including (1) subjects aged 4-10 years; (2) the subject has poor fine motor skills; (3) the subject is willing to follow modelling techniques by playing with playdough and positive reinforcement techniques from start to finish. The data collection technique in this research used the Frostig test during pretest and posttest. The data analysis technique used is the gain score and the U-Mann Withney test. The results of data analysis obtained a significance value of 0.047 (p<0.05), which means that playdough modelling techniques and positive reinforcement techniques affect increasing fine motor skills in children.